Odpowiedzialność człowieka za przyrodę w ujęciu Bazylego Wielkiego - Ewa Osek (Vox Patrum, 2007)
According to St. Basil the human condition and the State of nature are always the same. The histories of the mankind and natural world are closely connected, because of his conception of the nature, conceived as the whole of which a man is a part. St. Basil basing himself on the Scriptures divides the word history into three stages: 1) the Paradise age, 2) the times after the Fali, and 3) eschatological timeless future. The first age of history - the Paradise - was the time of perfection of human race (represented by Adam and Eve) and of incorruptibility of their natural environment. There was no death, no desease, no disasters. The human condition was very high, because Adam was the king of the nature. His dominion over the earth and the animals was very kind and gentle. The first people were vegetarians and they didn’t kill animals. The Paradise man’s perfectibility corresponded to the perfect State of Paradise plants (for example, a rose had no thoms), to the gentleness of all the animals, and to mildness of the climate. The origin of death and all disasters was the Fali of Adam. St. Basil said that the duty of Adam was everlasting, never-ending contemplation of God, whose novice Adam could hear. But Adam ceased his ascetic practice because of temptation of boredom and sadness. Immediately after the first Adam’s sin started the times of imperfection, corruption, and death. The age of the Paradise happiness has gone, and now, in our times, everywhere there is pain, illness, pollution, climatic anomalies, etc. Man is not already the king of nature: now he is just a steward of God. The good stewardship will be rewarded by God after the Last Judgement and the prize will be eternal salvation or return to the eschatological Paradise. But succeeding generations of people sin in much more terrible manner then Adam, and their crimes, called progress, waste the earth by causing further degeneration and pollution of environment. These bad stewards will be punished in Heli among the lightless fire and the worms eating their bodies. The sins of bad stewards will cause condemnation of some part of nature with them, because the human beings won’t can exist without their natural environment even in eschatological endless Heli. The consummation of the world won’t be the end of existence of nature. After this eschatological event nature will be still exist in some transfigured and spiritual “better shape” except for the lightless fire and worms going to be punished with the reprobates in the Heli, parallel to the higher State of human souls (called by St. Paul “new creation”). Then, man’s responsibility for natural world can be called eschatological or eternal.